Inhibitory effects of melatonin on neural lipid peroxidation induced by intracerebroventricularly administered homocysteine - Baydas, G; Kutlu, S; Naziroglu, M; Canpolat, S; Sandal, S; Ozcan, M; Kelestimur, H (Blackwell Munksgaard, 2003)
Melatonin, the main secretory product of the pineal gland, has been shown to be potentially effective in prevention of numerous types of neurodegenerative disorders in which free radical processes are involved. Homocysteine (Hcy), an independent risk factor for atherosclerosis, undergoes auto-oxidation and generates reactive oxygen species. The purpose of this study was to test whether intracerebroventricular (ICV) injection of Hcy leads to neural lipid peroxidation and also to investigate the protective effects of melatonin on the brain tissue from oxidative stress of Hcy. Adult male Wistar rats under anaesthesia were injected ICV with Hcy at a dose of 143 mu g/kg. Melatonin was administered intraperitoneally to a group of rats for three consecutive days before Hcy injection. The rats were decapitated and brain tissues were removed and hippocampus, cortex and cerebellum were dissected. There was a significant development of oxidative stress as indicated by an increase in malondialdehyde in hippocampus, cortex and cerebellum of rats injected with Hcy, whereas melatonin prevented the elevation of lipid peroxidation. Furthermore, melatonin significantly increased glutathione levels and glutathione peroxidase activity in all brain regions. The present study demonstrates that Hcy, in high levels, may be a causal factor in generation of free radicals in the brain and it may be one of the mechanisms which cause neurodegeneration in elderly people. It also shows that melatonin could potentially be beneficial in prevention of neurodegeneration caused by hyperhomocysteinemia.
Keywords: glutathione; GSH-Px; Homocysteine; LPO; Melatonin